Phaenandrogomphus safei, a new species from Sabah, northern Borneo (Odonata: Anisoptera: Gomphidae) - Dow, Rory A.; Luke, Sarah H. (Zootaxa, 2015)
Phaenandrogomphus safei is described from a male from the Kalabakan Forest Reserve, Sabah, Malaysian Borneo. It is the first species of Phaenandrogomphus to be recorded from Borneo. Onychogomphus treadawayi, known from Busuanga Island in the Palawan region of the Philippines, is transferred to Phaenandrogomphus.